Leptospira spp. infection in sheep herds in southeast Brazil - Barbante, Priscila [UNESP] (2014)
Background: With the aim of studying Leptospira spp. infection in sheep herds, blood samples and respective kidney and liver fragments were collected from 100 animals from twenty different properties during slaughter at a meat company in the Sorocaba region, Sao Paulo state, southeast Brazil. The microscopic agglutination test (MAT) was performed with 29 strains of Leptospira spp. To identify the agent in the liver and kidney, 100 samples of each tissue were submitted to culture in Fletcher medium and analyzed by the polymerase chain reaction (PCR) for Leptospira spp.Results: MAT detected 23 samples serologically positive for one or more Leptospira spp. serovars and significantly more for Autumnalis. Eight (4%) samples were positive in culture (four kidneys and four livers), corresponding to five animals with positive serology (one animal simultaneously positive for both kidney and liver) and two negatives. PCR detected Leptospira spp. in 14 samples (seven kidneys and seven livers) corresponding to 12 positive animals (two animals simultaneously positive for kidney and liver), of which ten were serologically positive and two negative.Conclusions: PCR was faster, more practical and more sensitive than culture for detecting leptospires. The results reinforce the importance of sheep in the epidemiological context of leptospirosis.